Pengaruh Tanggung Jawab Sosial, Kerakteristik Usaha, Religiusitas Terhadap Peningkatan Omzet Usaha Z-Mart (Studi BAZNAS Provinsi Bengkulu) - Herianto, Satria; Arisandy, Yosy; Sumarni, Yenti (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2025)
This study aims to determine the effect of social responsibility. business characteristics, religiosity on increasing z-mart business turnover, Z-Mart Program is a productive zakat program held by BAZNAS to empower mustahik through the provision of business capital and entrepreneurship training. The purpose of this research is economic empowerment in the form of developing stalls / shops owned by mustahik with a micro to small scale to overcome poverty and turn mustahik into muzaki. This research uses quantitative methods of data collected through distributing questionnaires. Respondents in this study were 50 people who met the criteria, namely mustahik beneficiaries of the z-mart program. Hypotheses are formulated or tested using multiple regression analysis. The results of this research indicate that there is an influence of social responsibility, business characteristics, religiosity on increasing z-mart business turnover. Amounted to 0.656 which means 65.6% while the remaining 34.4% is influenced by other variables outside the model that have not been studied.